Determination of additives in polymers and rubbers - Crompton, T. R. (Rapra Technology, 2007)
This book is designed as a practical text for use in the laboratories of the plastic producer and user industries and by others such as universities and institutions who are concerned with problems associated with additives and adventitious impurities in polymers. For example, powerful new analytical tools have been made available to the chemist by a combination of various chromatographic techniques with methods of identifying separated additives and their degradation products by techniques based on infrared and mass spectrometry. In particular supercritical fluid chromatography combined with m.
Keywords: Polymers -- Additives.; Rubber -- Additives.; Polymers -- Analysis.; Rubber -- Analysis.; elektronické knihy; electronic books